Histopathological Study on The Effect of Neuregulin-1 Against Cardiotoxicity Induced By Trastuzumab in Adult Mice - yousuf gays majeed; mustafa ghazi al-abbassi; ghaith ali jasim al-zubaidy (College of Pharmacy / Mustansiriyah University, 2018)
Objective: This work carried out to investigate the potential therapeutic effect of Neuregulin-1 against cardiotoxicity induced by trastuzumab in male mice. Materials and Methods:  Forty five adult male and female mice (weighing 35-50 gm) were divided into 3 groups randomly, each group contains 15 animals, group A which received distilled water as control by using intraperitoneal injection (IP) route for 10 days group B, received Trastuzumab as 6 mg/kg/day by using intraperitoneal injection route for 10 days while group C, received Neuregulin-1 (2.5 mg/day/animal) just before the administration of Trastuzumab (6mg/kg/day) given by IP route for 10 days. The significance of difference were tested by using ANOVA followed by Tukey test. Statistical significance depends on the P<0.05. Results: The histological score of cardiac tissue changes showed that a highly increase in mice administrated with trastuzumab when compared to control group while pretreatment with Neuregulin-1 , made a decrease in histological changing score when compared with trastuzumab group. The percentage of immunohistochemical score of stain uptake for TNF-α and IL-1β expression in cardiac tissue shows a highly increase in mice administrated when compared with control group, furthermore, pretreated with neuregulin-1 showed a decrease in the percentage of staining when compared with trastuzumab group. Conclusion: Neuregulin-1 can be used as a cardioprotective in cardiac complications of cancer treatment by its ability to attenuate the cardiotoxic effect of trastuzumab by decreasing in histological changing score and decrease in the percentage of staining when compared with trastuzumab group.